Perlindungan Hukum Kreditur dan Debitur dalam Pelayaran di Indonesia - Situmeang, Ampuan; Polim, Taufik (Universitas Internasional Batam, 2019)
Indonesia's strategic sea location is one of the most demands by local and foreign shipping. Shipping becomes an element of nation's economy and government?s concern. This is proven by the issuance of Law No. 17 of 2008 concerning Shipping which regulates implementation, legal protection of community, especially shipping companies, both debtors and creditors, judges, trustees and related institutions. Yet, it cannot implement effectively because Article 223 of Law No. 17 does not have a Ministerial Regulation governing the procedures for its implementation, consequently it disadvantages and leads to a loss for creditors and debtors. This study uses a normative legal research method which examines the secondary materials which is supported by a primary data. The Progressive Legal Theory is used by this study. It argues that there must be a procedure which links the implementation of shipping claims and the legal actors both creditors - debtors, judges and harbourmaster. They must pay attention to ethics and procedures in making decisions. In this regard, a Ministerial Regulation governing the claim procedures must be established.